Modelo Prolab: Ultra Life, una línea de productos de construcción sostenible a partir de residuos sólidos reciclados - Bocanegra Ocampo, Darwin Segundo (2024)
The problem identified in the Peruvian housing sector shows that 44.2% of homes are not built with durable materials, negatively impacting the security and quality of life of the inhabitants. Difficulty accessing quality, affordable building materials exacerbates this problem, limiting families' ability to improve their housing conditions in a safe and sustainable manner. ULTRALIFE emerges as an innovative solution by offering bricks, roof panels and walls made from recycled materials, intended for sustainable construction and remodeling. By lowering carbon emissions, this strategy not only helps the environment but also offers families wishing to upgrade their living space a more sustainable and accessible choice. Analysis of ULTRALIFE's value proposition demonstrates that its products meet the needs and expectations of users, particularly in terms of sustainability, economy and aesthetics. These goods are made to satisfy the needs of a consumer base that is becoming more conscious of how its building decisions affect the environment. With an Internal Rate of Return (IRR) of 160.50% and a Net Present Value (NPV) of S/4,891,090.84, ULTRALIFE exhibits strong economic viability from a financial standpoint. Weighted Average Cost of Capital (WACC) is 8.59%, and S/369,560.00 soles is the necessary initial investment. These numbers show the project's profitability as well as its capacity to produce large returns on investment. With a social NPV of S/6,182,098.91, the ULTRALIFE initiative also has a large social impact, which underlines its contribution to social improvement through sustainable construction. This value reflects the net social benefit generated, far exceeding the costs and initial investment, and confirms that ULTRALIFE is a viable project both economically and socially.